Impact of Internet-Based Cognitive Behavioral Therapy on University Students’ Mental Health and Loneliness During COVID-19 Self-Isolation (International Journal of Nursing Education, 2025)
Background: This study examined the effectiveness of an internet-based cognitive behavior therapy (iCBT) in alleviating loneliness and mental health issues in university students during the COVID-19 pandemic. Methods: An iCBT program was developed and implemented with 186 students from August 2020 to February 2021. It included a 30-minute psychoeducation video created on YouTube and the column method to assess cognitive restructuring. The participants completed five columns over seven days using the university’s academic information system. The evaluation tools included PHQ-9, GAD-7, and UCLA Loneliness Scale for depression, anxiety, and loneliness, respectively, and IES-R scales measuring decreases in academic and class motivation. The participants were randomly assigned to the intervention group and the control groups. Re-sults: The intervention group showed significantly lower scores than the control group in "Intrusion symptoms," "Avoidance symptoms," "Hyper-arousal," "PTSD," "depression," "anxiety," and "loneliness." Additionally, significant improvements were observed in the intervention group's "depression," "loneliness," and "decreased learning motivation," including "decline in class motivation" and "total decline in learning motivation" after the intervention. Conclusion: These results demonstrated that the iCBT intervention effectively reduced loneliness, PTSD symptoms, depression, and anxiety, and also enhanced learning motivation. Thus, iCBT may effectively alleviate loneliness and mental health issues associated with self-isolation during pandemics.
Keywords: COVID-19; student mental health; loneliness; internet cognitive behavioral therapy (iCBT)